(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Evaluation of the objects in the mineral resources sector depend on type of the legislative framework for the different stages of exploration process. The article covers to problems of legal and evaluation to objects of subsoil usage according to different stages of geological exploration in International Financial Reporting Standard 6 «Exploration for and Evaluation of Mineral Resources», Russian Financial Standard 24/2011 « Cost accounting of the mineral resources deployment», US GAAP and other normative documents. The results present the possibility of capitalizing mineral reserves as assets in mining oil and gas companies.